Liver-Targeted Combination Therapy Basing on Glycyrrhizic Acid-Modified DSPE-PEG-PEI Nanoparticles for Co-delivery of Doxorubicin and Bcl-2 siRNA - Tian, Guixiang; Pan, Ruiyan; Zhang, Bo; Qu, Meihua; Lian, Bo; Jiang, Hong; Gao, Zhiqin; Wu, Jingliang (Frontiers in Pharmacology, 2019)
Combination therapy based on nano-sized drug delivery system has been developed as a promising strategy by combining two or more anti-tumor mechanisms. Here we prepared liver-targeted nanoparticles (GH-DPP) composed of 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-polyethylene glycol-polyetherimide (DSPE-PEG-PEI) with Glycyrrhetinic acid-modified hyaluronic acid (GA-HA) for co-delivery of doxorubicin (DOX) and Bcl-2 siRNA. Particles size, zeta potential and morphology were determined for the drug-loaded GH-DPP nanoparticles (siRNA/DOX/GH-DPP). Cellular uptake and in vitro cytotoxicity were analyzed against HepG2 cells. In vivo bio-distribution and anti-tumor therapeutic effects of siRNA/DOX/GH-DPP were evaluated in H22-bearing mice. The results showed that siRNA/DOX/GH-DPP nanoparticles were nearly spherical and showed dose-dependent cytotoxicity against HepG2 cells. Compared to Glycyrrhetinic acid-free co-delivery system (siRNA/DOX/DPP) and GH-DPP nanoparticles for delivery of DOX or Bcl-2 siRNA alone, siRNA/DOX/GH-DPP nanoparticles could induce more cellular apoptosis, and showed higher anti-tumor effect. Herein GH-DPP nanoparticles could simultaneously deliver both chemotherapy drugs and siRNA into the tumor region, exhibiting great potential in anti-tumor therapy.